2016
DOI: 10.1530/eje-16-0172
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and methodological quality of meta-analyses on diabetes mellitus treatment: a systematic review

Abstract: Objective: Well-conducted meta-analyses (MAs) are considered as one of the best sources of clinical evidence for treatment decision. MA with methodological flaws may introduce bias and mislead evidence users. The aim of this study is to investigate the characteristics and methodological quality of MAs on diabetes mellitus (DM) treatments. Design: Systematic review. Methods: Cochrane Database of Systematic Review and Database of Abstract of Reviews of Effects were searched for relevant MAs. Assessing methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…This suggests that in many areas, the methodological quality of SR is low or critical low. Also, the overall methodological quality of 42 thematically diverse MA published in the Cochrane Library to April 2018 was low . Whereas in two studies, 50% of the included SR were assessed as “moderate” and “high” quality .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This suggests that in many areas, the methodological quality of SR is low or critical low. Also, the overall methodological quality of 42 thematically diverse MA published in the Cochrane Library to April 2018 was low . Whereas in two studies, 50% of the included SR were assessed as “moderate” and “high” quality .…”
Section: Discussionsupporting
confidence: 77%
“…The SR/MA's quality seems to be low in many fields of medicine. Among studies published in medicine to September 2019, in which the AMSTAR 2 was used as an instrument to evaluate the quality of SR/MA, 23 of 31 papers produced results similar to our study . In the six studies, the methodological quality of most (around 60%) of SRs was critical low to low .…”
Section: Discussionsupporting
confidence: 70%
“…Only four included studies provided their list of excluded studies (6.3%) [ 41 , 46 48 ], which was inferior to most other medical fields, except for nursing, pulmonary and diabetes mellitus treatment [ 5 , 6 , 18 ]. Journals generally limit the space available to publish the list of excluded studies, but some provide unlimited space (often online) to publish the list of excluded studies as supplementary material.…”
Section: Discussionmentioning
confidence: 99%
“…Any disagreement in the process of study selection or data collection was discussed, resolved by consensus, or determined with a third reviewer (JL). Ten bibliographical characteristics that have been suggested to influence the methodological quality of SRs from previous studies [ 6 , 17 , 18 ] and mod-AMSTAR sub-items were collected for each eligible review. We retrieved the impact factors (IFs) of the included reviews by searching the Journal Citation Reports in Web of Science (reviews published in English) and CNKI (reviews published in Chinese), specifically the IFs of the corresponding review publication year.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus is a severe glucose-associated metabolic disease that presents obvious genetic heterogeneity and frequently induces chronic damages of other tissues due to insulin secretion defects or/and biological function damage (1). Diabetes mellitus often results in ophthalmic diseases, cardiovascular disease and metabolic syndrome (2,3). A previous study indicated that diabetes mellitus may be regarded as a risk factor for incident chronic renal failure based upon a systematic review and meta-analysis (4).…”
Section: Introductionmentioning
confidence: 99%